Simulasi Mikro Combine Magnetik pada Pembelajaran di Sekolah Dasar - Kiftirul Aziz (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Obtaining alternative energy without ignoring non-renewable energy is a vital problem that demands immediate solutions. Judging from the function of learning media, Microcombinemagnetic media has performed its function in facilitating students' understanding to absorb the essence of learning related to the use of alternative energy without fossil materials. The purpose of using Microcombinemagnetics is to improve students' understanding of the PLMTH concept and make it easier for teachers to convey the PLMTH concept and material related to the PLMTH concept. This study method refers to best practices written based on the best experiences in solving a problem in the classroom. The results achieved through Microcombinemagnetic simulations include: (1) the social, cultural, and economic diversity of society, the class average of 88; (2) in the explanatory / scientific explanation text material, the mean score of grade VI A students is 6 points above the KKM; (3) in the material on how to produce, distribute, and save electrical energy, the average score of the students is 81; and (4) on the material on Indonesia's role in cooperation in various fields within the scope of ASEAN, the average student score reached 82.The conclusion obtained from this study is that Microcombinemagnetic simulation on learning the theme of globalization, the sub-theme of globalization around me, produces an average range. between 76 and 88.